Artifacts Generated During Azoalkane Peroxy Radical Oxidative Stress Testing of Pharmaceuticals Containing Primary and Secondary Amines. Issue 12 (13th November 2015) - Nefliu, Marcela; Zelesky, Todd; Jansen, Patrick; Sluggett, Gregory W.; Foti, Christopher; Baertschi, Steven W.; Harmon, Paul A.
Abstract : We report artifactual degradation of pharmaceutical compounds containing primary and secondary amines during peroxy radical‐mediated oxidative stress carried out using azoalkane initiators. Two degradation products were detected when model drug compounds dissolved in methanol/water were heated to 40°C with radical initiators such as 2, 2′‐azobis(2‐methylpropionitrile) (AIBN). The primary artifact was identified as an α‐aminonitrile generated from the reaction of the amine group of the model drug with formaldehyde and hydrogen cyanide, generated as byproducts of the stress reaction. A minor artifact was generated from the reaction between the amine group and isocyanic acid, also a byproduct of the stress reaction. We report the effects of pH, initiator/drug molar ratio, and type of azoalkane initiator on the formation of these artifacts. Mass spectrometry and nuclear magnetic resonance were used for structure elucidation, whereas mechanistic studies, including stable isotope labeling experiments, cyanide analysis, and experiments exploring the effects of butylated hydroxyanisole addition, were employed to support the degradation pathways. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:4287–4298, 2015